Refugees and the post-migration environment - Fazel, M (BioMed Central, 2018)
The ever-increasing number of reasons forcing people to flee from their homes to new, safer places either within their countries of origin, into neighbouring countries or across continental, conversant and cultural boundaries has led to a humanitarian crisis to which scientific enquiry must increasingly contribute. Yet, little is known about how best to support refugee adults and children in the process of resettling in high-income nations, an issue which the recent study by Lau et al. published in this journal, is attempting to address. Their study highlights how refugee parents, children and adolescents report good child mental health and adjustment approximately 3–4 years after gaining humanitarian visa status to remain in Australia. Herein, the need to support parenting capability and to facilitate public policy to work within an evidence-based framework are discussed.